Anti-inflammatory and Anti-HIV Compounds from Swertia bimaculata - Dong, Miao; Quan, Li-Qiu; Dai, Wei-Feng; Yan, Shi-Li; Chen, Chin-Ho; Chen, Xuan-Qin; Li, Rong-Tao (Planta Medica, 2017)
Three new compounds (1 – 3), including a sesterterpenoid, aspterpenacid C (1), with an unusual 5/3/7/6/5 pentacyclic skeleton, together with seven known ones (4 – 10), were isolated from the ethanol extract of the traditional Chinese medicinal plant Swertia bimaculata. Their structures were elucidated on the basis of the methods of spectroscopic NMR, MS, and computational chemistry. The structure of 1 was further confirmed by single-crystal X-ray diffraction analysis. Compounds 1 – 10 were tested for activities on the inhibition of nitric oxide production and HIV-1 replication in vitro. Compound 1 exhibited moderate activity in inhibiting nitric oxide production (IC50 = 16.1 µM) and HIV-1 replication (EC50 = 1.35 µM).
Keywords: sesterterpenoid; Swertia bimaculata; Gentianaceae; anti-inflammation; anti-HIV